Why Do Short Sellers Like Qualitative News?. (21st April 2017) - von Beschwitz, Bastian; Chuprinin, Oleg; Massa, Massimo
Abstract : Short sellers trade more on days with qualitative news, that is, news containing fewer numbers. We show that this behavior is not informationally motivated but can be explained by short sellers exploiting higher liquidity on such days. We document that liquidity and noise trading increase in the presence of qualitative news, enabling short sellers to better disguise their informed trades. Natural experiments support our findings. Qualitative news has a bigger effect on short sellers' trading after a decrease in liquidity following the stock's deletion from the Standard & Poor's 500 index and a smaller effect when investor attention is distracted by the Olympic Games.